El clorpirifos : posible disruptor endocrino en bovinos de leche (2004)
ABSTRACT: The use of pesticides for the control of those insects, fungi or plants that negatively affect or compete with animals or crops has allowed a remarkable increase in agricultural yield and cattle production. Nonetheless, the harmful effects of pesticides on human and environmental health have already been demonstrated and have become a major issue since the discovery of the role of pesticides as endocrine disrupters (ED). This name is given to substances that interfere with the synthesis, secretion, transport, union, action or elimination of natural hormones. The study of ED has received a great interest in the last two decades, not only because its consequences for public health through residues and contamination of food, but also because several pesticides have been related to reproductive problems in animals. The present review begins with a description of the current state of the use of insecticides (especially organophosphates) in farming production in Colombia, then, it examines up to date information regarding ED, their effects, and mechanisms discovered so far. It is evident the lack of information related to EDs in cattle, compared to the amount available on other species, especially wild animals and humans. Chlorpyrifos is an organophosphate insecticide, widely used in dairy cattle industry in Colombia. It has been reported to affect thyroid hormones and there is contradictory information regarding its effects upon estrogen. This review emphasizes the need to research the potential role of chlorpyrifos as an ED in the dairy region of the north of Antioquia, Colombia, to identify the possible relations between chlorpyrifos residues in milk and plasmatic levels of thyroid hormones and estrogens in dairy cows, as well as developing in vitro models for its study.